2020
DOI: 10.1002/chem.202000067
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Construction of Alkaloids by Employing a Key ω‐Transaminase Cascade

Abstract: An ω‐transaminase‐triggered intramolecular aza‐Michael reaction has been employed for the preparation of cyclic β‐enaminones in good yield and excellent enantio‐ and diastereoselectivity, starting from easily accessible prochiral ketoynones and commercially available enzymes. The powerful thermodynamic driving force associated with the spontaneous aza‐Michael reaction effectively displaces the transaminase reaction equilibrium towards product formation, using only two equivalents of isopropylamine. To demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…This methodology has recently seen expansion to alkyne equivalents, generating exo-cyclic enamines. 42 In the follow-up manuscript to this work, O'Reilly and coworkers again demonstrate how enzyme selectivity may be exploited to perform this challenging retrosynthetic disconnection through the use of an ADH to deliver a range of tetrahydropyrans and tetrahydrofurans, moieties that are both challenging to incorporate into synthesis and readily present in bioactive molecules. 41 Analysis of the products described across the two manuscripts resulting from this biocatalytic methodology reveals that the heterocycles obtained present an opportunity to cover a wide region of chemical space.…”
Section: Biocatalysis For Fragment Synthesismentioning
confidence: 96%
“…This methodology has recently seen expansion to alkyne equivalents, generating exo-cyclic enamines. 42 In the follow-up manuscript to this work, O'Reilly and coworkers again demonstrate how enzyme selectivity may be exploited to perform this challenging retrosynthetic disconnection through the use of an ADH to deliver a range of tetrahydropyrans and tetrahydrofurans, moieties that are both challenging to incorporate into synthesis and readily present in bioactive molecules. 41 Analysis of the products described across the two manuscripts resulting from this biocatalytic methodology reveals that the heterocycles obtained present an opportunity to cover a wide region of chemical space.…”
Section: Biocatalysis For Fragment Synthesismentioning
confidence: 96%
“…In addition, the use of an excess of an amino donor is perhaps the easiest way to shift the equilibrium toward product formation [ 12 , 13 , 14 ]. In the last few decades, a number of academic and industrial examples using ATAs for chiral amine production have been reported in the literature [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the TD and OATA cascade reaction, the reaction catalyzed by TD was much faster than that of OATA. Asymmetric synthesis of chiral amines using OATA has suffered from an unfavorable reaction equilibrium when a high concentration of substrate was used [ 13 15 ]. Therefore, OATA determines the conversion yield of the whole process.…”
Section: Introductionmentioning
confidence: 99%